2007
DOI: 10.1016/s1001-0742(07)60012-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in soils around a lead and zinc mine

Abstract: Five samples of soil collected from a lead and zinc mine were used to assess the effect of combined contamination of heavy metals on soil bacterial communities using a polyphasic approach including characterization of isolates by culture method, community level catabolic profiling in BIOLOG GN microplates, and genetic commuruty fingerprinting by denaturing gradient gel electrophoresis of 16s rDNA fragments amplified by PCR from community DNA ( P C R -W E ) . The structure of the bacterial community was affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…However, these are likely to be second order influences within ecosystems, which are predominantly driven by geogenic factors. High concentrations of metals, for example in soils exposed to industrial pollution or mining, substantially alter microbial communities (Baker and Banfield 2003;Hu et al, 2007;Kock and Schippers, 2008;Denef et al, 2010). Similarly, amendment of soils with Cu, Pb, Zn and Cd strongly influences resident bacterial communities (B氓氓th, 1989;Abaye et al, 2005;Wakelin et al, 2010 a, b).…”
Section: Introductionmentioning
confidence: 99%
“…However, these are likely to be second order influences within ecosystems, which are predominantly driven by geogenic factors. High concentrations of metals, for example in soils exposed to industrial pollution or mining, substantially alter microbial communities (Baker and Banfield 2003;Hu et al, 2007;Kock and Schippers, 2008;Denef et al, 2010). Similarly, amendment of soils with Cu, Pb, Zn and Cd strongly influences resident bacterial communities (B氓氓th, 1989;Abaye et al, 2005;Wakelin et al, 2010 a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies showed decreasing number of DGGE bands with increasing levels of metal pollution, indicating altered microbial communities (Wang et al, 2007a;Hu et al, 2007;Khan et al, 2007). Inverse relationship between band patterns and concentrations of Pb and Cd in soils that were contaminated with mine tailings has been reported (Hu et al, 2007;Khan et al, 2007). Using this technique, similar finding was reported by Sobolev and Begonia (2008) at low concentration of Pb, adding that the reduction was steady after radical increase in metal concentration from 0-2000 mg kg -1 .…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge) and Temperatumentioning
confidence: 56%
“…This technique has been used extensively in the analysis of the impact of metal contamination to soil microbial population and diversity. Most of these studies showed decreasing number of DGGE bands with increasing levels of metal pollution, indicating altered microbial communities (Wang et al, 2007a;Hu et al, 2007;Khan et al, 2007). Inverse relationship between band patterns and concentrations of Pb and Cd in soils that were contaminated with mine tailings has been reported (Hu et al, 2007;Khan et al, 2007).…”
Section: Denaturing Gradient Gel Electrophoresis (Dgge) and Temperatumentioning
confidence: 99%
“…Arsenic-, cadmium-, copper-and zinc-resistant bacteria were isolated from gold, lead-zinc, copper and silver mine soils, respectively (Li et al 2013;PiotrowskaSeget et al 2005;Zhu et al 2012). Heavy metal tolerance of the microbial community in these environments could be acquired by genetically tolerance elements (genes involving in metal resistance are mostly presented in plasmids) and shift in species composition (Hu et al 2007). More than 90 % of bacterial strains obtained from Pb ore in this study could tolerate at least 100 ppm Pb.…”
Section: Mic Determination and Selection Of Pb-absorbing Bacteriamentioning
confidence: 99%